MARKETING STRATEGY FACTORS AFFECTING THE DECISION TO STUDY AT THE BACHELOR DEGREE LEVEL RETAIL BUSINESS PROGRAM, FACULTY OF MANAGEMENT SCIENCE, NAKHON SI THAMMARAT RAJABHAT UNIVERSITY - Nualsut, Samaporn; Promkum, Sujinda; Phetburi, Wanwisa; Werasuk, Seksan (Journal of MCU Nakhondhat, 2021)
The Objectives of this research article were to 1) the factors and marketing strategies that affect the decision to study for a bachelor's degree in Retail Business Faculty of Management Nakhon Si Thammarat Rajabhat University And 2) to study the relationship between types of educational establishments and the factors of marketing strategies that affect the decision to study at the bachelor's degree in Retail Business Faculty of Management Nakhon Si Thammarat Rajabhat University. This research is a quantitative research. The sample is 70 retail business students that were randomly sampled. And using questionnaires as a tool to collect the data. The statistics were percentage, mean, standard deviation and T - Test. The value of the research was as follows: 1) The general data of the sample were mostly female. As for the study group, it was found that most of them learned theory at university first And in the type of school that graduated, most of them were government schools. 2) The marketing strategies affecting the decision to study at the bachelor's degree in Retail Business Faculty of Management Nakhon Si Thammarat Rajabhat University was at a high level. And 3) the relationship between types of educational establishments that graduate and the factors of marketing strategy that affect the decision to study at the bachelor degree in Retail Business Faculty of Management Nakhon Si Thammarat Rajabhat University found the variance of the marketing strategy factors influencing the decision to study at the bachelor's degree in Retail Business Faculty of Management Nakhon Si Thammarat Rajabhat University overall was not different Statistically significant at 0.05.